Studi Perbandingan Jenis Sumber Air Terhadap Daya Tarik Nyamuk Aedes aegypti Untuk Bertelur - Mawardi Mawardi; Rika Busra (Jurnal Serambi Engineering, 2019)
Dengue Hemorrhagic Fever (DHF) is an endemic disease caused by a virus and transmitted by vectors, especially Aedes aegypti and Ae. Albopictus. The number of cases tends to increase and is widespread in almost all regions. This study aims to determine the different types of water sources on the attractiveness of Aedes aegypti for laying eggs. The research method uses the One Way Anova statistical test analysis with α 0.05. The results showed the One Way Anova test obtained p value = 0.048 (p 0.05) meaning that there are differences in the type of water source to the attractiveness of Aedes aegypti mosquitoes to lay eggs, especially in well water with river water with a value of p = 0.016 (p 0, 05). The difference in the number of mosquito eggs found in containers containing rain water, river water and well water indicates that the Aedes aegypti mosquito has different appeal in laying its eggs. The community should always maintain sanitation, especially containers that hold water so that it does not have the potential to become Aedes aegypti mosquito nest sites and can reduce the density of Aedes aegypti mosquitoes.